Non-Placement WIL: The Case of an Exercise Prescription Clinic - Hodges, Lynette; Martin, Andrew (Journal of University Teaching and Learning Practice, 2020)
Universities globally have continued to strategically increase work-integrated learning (WIL) opportunities for students to enhance graduate employability. However, meeting the needs of the increasing number of placements in industry settings places challenges on employers and academic programme coordinators. This paper examines an innovative teaching and learning initiative demonstrating non-placement WIL practice on-campus and online through an exercise prescription clinic (EPC). The benefits provided by these opportunities have not only been for student learning, but for clients, in particular those impacted by neurological and/or muscular skeletal problems. The development of the on-campus EPC has focused on key elements of good practice in WIL highlighted by Agnew, Pill and Orrell (2017). The recent Covid-19 pandemic and the related government restrictions have resulted in the on-campus EPC being flipped online, requiring adaptability and flexibility of both students and clients. This paper reinforces the importance of developing WIL experiences that enhance the learning outcomes for both the student and the client. It also highlights the transferability of authentic industry non-placement WIL clinical experiences for future health professionals to both on-campus and online settings, which enable students the opportunity to engage with a range of clients in a safe environment, enhancing both personal and professional learning outcomes.